2010
DOI: 10.1111/j.1365-2982.2010.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Appearance and disappearance of functional gastrointestinal disorders in patients with eating disorders

Abstract: Functional gastrointestinal disorders remain common after 12 months in patients with an ED. Considerable turnover of the FGIDs occurs, however, and the appearance of new FGIDs is not restricted to the original FGID regional category. There is no apparent relationship between the turnover of the FGIDs and ED behaviors, psychological variables or body weight change. These findings have implications for the clinical evaluation and management of FGIDs in ED patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 15 publications
1
57
1
1
Order By: Relevance
“…In terms of FGIDs, adult studies have demonstrated that even after 12 months of treatment, almost 80% of adults with AN continue to meet the criteria for FGIDs, 43 suggesting that FGIDs can persist independent of treatment outcome; however, in our study cohort, FGIDs were less common at T1 than has been reported in adults. Irritable bowel syndrome was the most common FGID in our patients with AN, and even this became less common after nutritional rehabilitation, suggesting that early intervention in a younger population may help prevent the development of long-term comorbidities.…”
Section: Discussioncontrasting
confidence: 69%
“…In terms of FGIDs, adult studies have demonstrated that even after 12 months of treatment, almost 80% of adults with AN continue to meet the criteria for FGIDs, 43 suggesting that FGIDs can persist independent of treatment outcome; however, in our study cohort, FGIDs were less common at T1 than has been reported in adults. Irritable bowel syndrome was the most common FGID in our patients with AN, and even this became less common after nutritional rehabilitation, suggesting that early intervention in a younger population may help prevent the development of long-term comorbidities.…”
Section: Discussioncontrasting
confidence: 69%
“…The literature provides consistent evidence that children with EDs have a high rate of gastrointestinal disorders and inflammatory bowel diseases (see Table ). Boyd, Abraham, and Kellow () and Boyd, Abraham, and Kellow () studies have found that 97–98% of inpatients with an ED had a gastrointestinal disorder, 53% had three or more gastrointestinal disorders, and 77% continued to have a gastrointestinal disorder at 12‐month follow‐up (Boyd et al, ). Children with AN specifically have a high rate of gastrointestinal disorders or symptoms (75–79%) compared to healthy children and the severity of AN is positively associated with gastrointestinal symptoms (Lee, Ng, Kwok, Thomas, & Becker, ; Perez, Coley, Crandall, Di Lorenzo, & Bravender, ).…”
Section: Resultsmentioning
confidence: 99%
“…Somatization has not been well deepened in the ED population, even if some studies have recently described the relationship between functional symptomatology and ED, in particular the gastroenteric functional symptoms [74,75]. From a clinical standpoint, it could be difficult to diagnose as organic or functional a gastrointestinal disease referred by ED patients; anyway it is well-known that ED patients’ body sensations – often inappropriately experienced – can influence the disease and its course [11].…”
Section: Discussionmentioning
confidence: 99%